The Caturalektis untuk Pengembangan Manajemen Pendidikan - Umar, Surip (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2024)
This study uses a qualitative approach with an analysis of thinking, about the management of Islamic educational institutions in terms of human resource competency. The purpose of the study is to provide problem solving for problems in the management of Islamic educational institutions based on scientific theory, in order to become eligible management to produce the essence to be achieved. The Caturalektis Theory is a solution for the management of Islamic Educational Institutions in their development and management which is only based on a person's natural experience without any scientific theory. The occurrence of inequality in the competence of educators which results in the problem of lack of vision, split personality and the problem of neglected values, this is one of the factors of the problematic human resource management problem, even though the values ​​of the pondok are the basis for the formation of the vision, mission, goals and activities of Islamic educational institutions. The solution to this problem is to apply Caturalektis in the development of expert theory trialektis. The importance of this theory as a solution and can be utilized by administrators in other Islamic educational institutions. Amin Abdullah's Interconnected Entities Theory is the right and rational solution for the development of Islamic educational institution management with the development of Caturalektis, to form eligible management. The essence targets will be achieved through: Hadharah an-nashi is monotheism to Allah through good parenting, hadharah al-ilmi is teacher competence through good education and teaching, hadharah falsafiyah is social ethics and universal characteristics through a good social and institutional economic approach. and finally hadharah Istiqrariyah with the target of consistency.